Using Actor-Based Theories Of Change to Conduct Robust Contribution Analysis in Complex Settings - and Koleros, Andrew; Mayne, John (Canadian Journal of Program Evaluation, 2019)
The use of theories of change (ToCs) is a hallmark of sound evaluation practice. As interventions have become more complex, the development of ToCs that adequately unpack this complexity has become more challenging. Equally important is the development of evaluable ToCs, necessary for conducting robust theory-based evaluation approaches such as contribution analysis (CA). This article explores one approach to tackling these challenges through the use of nested actor-based ToCs using the case of an impact evaluation of a complex police-reform program in the Democratic Republic of Congo, describing how evaluable nested actor-based ToCs were built to structure the evaluation.
Keywords: Behavioural strategy; COM-B